PENGAMATAN GEJALA INFEKSI Phytophthora palmivora PENYEBAB PENYAKIT BUSUK BUAH PADA KAKAO - Nurfianti; Umrah (Biocelebes, 2019)
Phytophthora palmivora is a patogen fungi causing pod rot disease in cacao plants. Thr researchof effectivity examination of biopesticide (active ingredient Aspergillus sp.) againts the growth of P. Palmivora in cacao pod (Theobroma cacao L.) by in vivo state was conducted from March 2018 to September 2018. This research was carried out in Sidondo Village, Dolo Subdistrict, Sigi Biromaru District, Central Sulawesi Province and Laboratory of Biotechnology, Faculity of Mathematics and Natural Sciences, Tadulako University. This study was aimed to determine an effective biopesticide (active ingredient Aspergillus sp.) which suppresses the growth of P. Palmivora in cacao pod by in vivo state and to stipulate the most affective biopesticide concentration (active ingredient Aspergillus sp.) in suppressing the growth of of P. Palmivora in cacao pod by in vivo state. This This research was by using the methods of Group Random Design (GRD) or Rancangan Acak Kelompok (RAK) consisting of six treatmentsand four repetitions. The observation parameters consist of symptoms of disease, the lenght of infection spots, the infection persentage of P. Palmivora, microscopic observations, in the microscopic of P. Palmivora. The results showed that the biopesticide (active ingredient Aspergillus sp.) was varified as effective in controlling P. Palmivora drawing the rot disease bin cacao plants, by the absent of any symptoms of infection P1,P2,P3,P4 dan P5 treatments. The only treatments in which was infected by P. Palmivora , drawing the rot disease in cacao plants, was P0 with the occurence time of infection symptoms was in the third day after inoculation, the average lenght of infection spots was 8,65 cm and the average infection persentage was 11,60%.